Field emission from oriented tin oxide rods - Deshpande, A. C.; Koinkar, Pankaj M.; Ashtaputre, S. S.; More, Mahendra A.; Gosavi, S. W.; Godbole, P. D.; Joag, Dilip S.; Kulkarni, S. K. (Thin Solid Films, 2006)
Tin oxide (SnO2) films were grown on silicon substrates by a wet chemical route. It was found from scanning electron microscopy investigations that oriented SnO2 rods normal to the substrates were obtained. Field emission studies were carried out in diode configuration in an all metal ultra high vacuum chamber at a base pressure similar to 1.33 x 10(-8) mbar. The `onset' field required to draw 0.1 mu A/cm(2) current density from the emitter cathode was found to be similar to 3.4 V/mu m for SnO2 rods. The field emission current and applied field follows the Folwer-Nordheim relationship in low field regime. The observed results indicate that the field emission characteristics of chemically grown SnO2 structures are comparable to the vapor grown nanostructures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: field emission; microstructures; scanning electron microscopy; tin oxide

Field emission studies of novel ZnO nanostructures in high and low field regions - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S.; Pillai, Vijayamohanan K. (Nanotechnology, 2006)
A study of the field emission characteristics of novel structures of ZnO, namely marigolds, multipods and microbelts, has been carried out in both the close proximity configuration and the conventional field emission microscope. The use of a conventional field emission microscope overcomes the drawback of arc formation at high field values. The nonlinearity in the Fowler - Nordheim ( F - N) plot, a characteristic feature of semiconductors has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability exhibited by these structures is also promising for future device applications.

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Field emission investigation of single Fe-doped SnO2 wire - Bhise, Ashok B.; Late, Dattatray J.; Sathe, Bhaskar R.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Solid State Sciences, 2009)
Tin oxide submicronwires doped with Fe element were prepared by the thermal evaporation method. Morphological and structural characterizations revealed wires with sub micron size and crystalline in nature. The field electron emission from the single Fe:SnO2 wire was carried out in conventional field emission microscope. The Fowler-Nordheim plot obtained from I-V characteristics of the wire showed a linear behavior typical that of metal. The field enhancement factor estimated from the slope of the F-N plot is 7455 cm(-1), indicating that the field emission is from nanometric features of the emitter. A current density of 10 A/cm(2) has been obtained at an applied field of 4.845 x 10(3) V/mu m. The field emission current-time record at a current level of 1 mu A for more than 3 h duration is promising for various field emissions based applications. (C) 2009 Published by Elsevier Masson SAS.
Keywords: Current stability; Fe doped; field emission; SnO2

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

Facile synthesis of Ag nanowire-rGO composites and their promising field emission performance - Samantara, Aneeya K.; Mishra, Dillip Kumar; Suryawanshi, Sachin R.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Jena, Bikash Kumar; Rout, Chandra Sekhar (RSC Advances, 2015)
Crystalline, ultra long silver nanowires (Ag NWs), few-layered rGO (reduced graphene oxide) and their rGO-Ag NW nanocomposite have been synthesized using a polyol reflux technique under optimized experimental conditions. The field emission performance of the rGO-Ag NW nanocomposite, rGO and Ag NW emitters was investigated. The turn on field required to draw an emission current density of similar to 1 mA cm(-2) was found to be similar to 5.00, 3.92 and 2.40 V mu m(-1) for the Ag NW, rGO and rGO-Ag NW nanocomposite emitters, respectively. The combined contribution of the sharp edges of the thin graphene sheets and high aspect ratio of the Ag nanowires, and their synergetic effect in the rGO-Ag NW nanocomposite, are responsible for the enhanced field emission behavior. First-principles density functional calculations show that the enhanced field emission may also be due to the overlapping of the electronic structures of the Ag NWs and rGO nanosheets.

Field emission properties of spinel ZnCo2O4 microflowers - Ratha, Satyajit; Khare, Ruchita T.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2015)
ZnCo2O4 microflowers were synthesized by a simple low temperature hydrothermal route. A single three-dimensional microflower consists of hundreds of self-assembled petals, with a thickness of several nanometers. These microflowers have exceptionally thin edges with a few petal layers. The ZnCo2O4 microflowers appeared to be stable and good field emitters.

Facile approach towards fabrication of GdB6-ZnO heteroarchitecture as high currentdensity cold cathode - Suryawanshi, Sachin R.; Mistari, Chetan D.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Chemistryselect, 2016)
Three dimensional (3D) GdB6-ZnO heteroarchitecture comprised of thin coating of GdB6 on self aligned ZnO urchins with pointed apex has been synthesized employing optimized Pulsed Laser Deposition (PLD) technique. The self aligned ZnO urchins on Zn substrate were obtained using hydrothermal route. The as-synthesized GdB6-ZnO heteroarchitecture was characterized using XRD, SEM, TEM XPS, and UPS in order to reveal its structural, morphological, chemical, and electronic properties. Interestingly, the GdB6-ZnO heteroarchitecture exhibits superior field emission (FE) behviour in contrast to the pristine ZnO urchins envisaged by extraction of very high emission current density of similar to 4.6 mA/cm(2) at an applied field of similar to 4.5 V/mm, against similar to 1.5 mA/cm(2) at an applied field of similar to 5.6 V/mm from the pristine ZnO urchins emitter. Furthermore, the GdB6-ZnOemitter exhibits good emission stability at pre-set value of similar to 5 mA over duration of more than 3 hours. The superior FE behaviour of the GdB6-ZnO is attributed to low work-function of GdB6 and presence of nanometric protrusions on the emitter surface, further enhancing the aspect ratio provided by the ZnO urchins. The present results demonstrate a facile approach towards fabrication of high current density cold cathodes due to rare earth hexaborides via designing hetero-architectures comprised of their well adherent ultrathin coating on high aspect ratio metal oxide nanostructures.

Field emission properties of highly ordered low-aspect ratio carbon nanocup arrays - Gupta, Bipin Kumar; Kedawat, Garima; Kumar, Pawan; Singh, Satbir; Suryawanshi, Sachin R.; Agrawal, Neetu; Gupta, Govind; Kim, Ah Ra; Gupta, R. K.; More, Mahendra A.; Late, Dattatray J.; Hahm, Myung Gwan (RSC Advances, 2016)
Herein, we design and develop a field emission device utilizing highly porous carbon nanocup (CNC) films. These three-dimensional (3D) low-aspect ratio CNC structures were fabricated by a combination of anodization and chemical vapor deposition techniques. The low turn-on fields of 2.30 V mu m(-1) were observed to draw an emission current density of 1 mu A cm(-2) and a maximum emission current density of similar to 1.802 mA cm(-2) drawn at an applied field of similar to 4.20 V mu m(-1). The enhanced field emission behavior observed from the CNC films is attributed to an excellent field enhancement factor of 1645. The observed field emission properties of CNC arrays are attributed to a synergistic combination of high aspect ratio, nano-sized radius of curvature, highly organized distribution of the emitters over the whole area of specimen and lower screening effect of the CNC arrays. These observations shed light on the effect of the stacking carbon layers of CNC on their electronic properties and open up possibilities to integrate new morphologies of graphitic carbon in nanotechnology applications. Thus, the low turn on field, high emission current density and better emission current stability enable CNC based future field emission applications.

Facile synthesis of nanocomposites of CNF-Sn and C-Sn microspheres: Prospective field emitter - Badadhe, Satish S.; Yadav, Poonam; Suryawanshi, Sachin; More, Mahendra A. (Journal of Alloys and Compounds, 2022)
We report synthesis of Carbon nanofibers (CNFs) and hybrid nanocomposites namely, CNF-Sn and C-Sn microspheres using simple electrospinning technique, followed by annealing in controlled atmosphere. The as-prepared materials were characterized using X-raydiffraction (XRD), Field emission scanning electron microscopy (FESEM), Transmission electron microscopy (TEM), Ultra-violet photoelectron spectroscopy (UPS), and Raman spectroscopy to reveal their physico-chemical properties. As carbon family members are potential materials for field emission (FE) based applications, owing to their high aspect ratio FE characteristics of the synthesized materials were explored at base pressure of 1 x 10(-8) mbar. Interestingly, the hybrid nanocomposite CNF-Sn and C-Sn emitters showed improved FE behavior (with the turn-on field of 3.4 and 1.36 V/mu m, respectively) in contrast to the pristine CNFs emitter (turn-on field of 5.4 V/mu m). Furthermore, the maximum emission current density is substantially enhanced, 7.75 and 4.6 mA/cm(2) for CNF-Sn and C-Sn emitters, respectively. The improvement in the FE behavior of nanocomposite emitters is attributed to the combined effect of morphology and modulation of electronic properties at the interface of nanocomposites. The results confirm that FE characteristics of pristine nanostructures can be greatly improved upon formation of their nanocomposites and this approach can be extended to other nanostructures for improving their multi-functionalities. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: carbon nanofiber; electrospinning; field emission; Nanocomposite; Tin